👤

Aduceti la forma ce mai simpla :
3(√12-2√27)
√48-2√3(2-5√12)
(3+√3)(2+√3)


Răspuns :

3(√12-2√27) =
=3(2√3-6√3) =
=
3(-4√3) =
=-12
√3

 √48-2√3(2-5√12)=
= 4√3-2√3(2-10√3)=
=
4√3-4√3+60=
=60

(3+√3)(2+√3) =

=6+2√3+3√3+3=
=9+5√3





[tex]3( \sqrt{12} -2 \sqrt{27} )=3(2 \sqrt{3} -6 \sqrt{3} )=3 \cdot (-4 \sqrt{3} )=-12 \sqrt{3} \\ \sqrt{48} -2 \sqrt{3} (2-5 \sqrt{12} )=4 \sqrt{3} -2 \sqrt{3} (2-10 \sqrt{3} )= \\ =4 \sqrt{3} -4 \sqrt{3} +60=60 \\ (3+ \sqrt{3} )(2+ \sqrt{3} )=6+3 \sqrt{3} +2 \sqrt{3} +3=9+5 \sqrt{3} [/tex]